2020
DOI: 10.1016/j.bbi.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of neuropsychiatric manifestations in COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
2
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 29 publications
5
197
2
17
Order By: Relevance
“…There is growing literature showing that patients with COVID-19 may have neuropsychiatric manifestations. In a recent series, anxiety, mood disorders, emotional state symptoms, sleep disorders, and suicidal ideation have been reported in about 13% of COVID-19 patients [ 21 ]. In a nationwide, cross-specialty surveillance study of acute neurological and psychiatric complications of COVID-19, 25% were identified with altered mental status, reflecting both neurological and psychiatric diagnoses, such as encephalitis and psychosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing literature showing that patients with COVID-19 may have neuropsychiatric manifestations. In a recent series, anxiety, mood disorders, emotional state symptoms, sleep disorders, and suicidal ideation have been reported in about 13% of COVID-19 patients [ 21 ]. In a nationwide, cross-specialty surveillance study of acute neurological and psychiatric complications of COVID-19, 25% were identified with altered mental status, reflecting both neurological and psychiatric diagnoses, such as encephalitis and psychosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations such as insomnia, anxiety, post-traumatic stress symptoms (PTSD), psychosis and mood disorders have been described in several reports (see Table 1; Dinakaran et al, 2020;Liguori et al, 2020;Nalleballe et al, 2020;Rogers et al, 2020;Romero-Sanchez et al, 2020;Vindegaard and Benros, 2020). A study that retrieved data from a global health collaborative platform that included medical records of 40,469 COVID-19 positive cases, mostly from the United States (US) (76%), found that 22.5% had neurological and/or psychiatric manifestations, being anxiety and related disorders the most prevalent (4.6%) (Nalleballe et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 99%
“…However, the TriNetX platform allows analysis in the form of queries. The TriNetX platform has previously been described in detail in several similar studies on COVID-19 that used this platform [3,8,9,10,11]. At University of Arkansas for Medical Sciences, the data from TriNetX is managed by the Arkansas Clinical Data Repository (AR-CDR) and maintained by the Department of Biomedical Informatics.…”
Section: Data Sourcementioning
confidence: 99%